2022
DOI: 10.3390/v14050952
|View full text |Cite
|
Sign up to set email alerts
|

Andrias davidianus Ranavirus (ADRV) Genome Replicate Efficiently by Engaging Cellular Mismatch Repair Protein MSH2

Abstract: As nucleocytoplasmic large DNA viruses, replication of ranaviruses (genus Ranavirus, family Iridoviridae) involves a series of viral and host proteins. We have described that the replication and transcription machinery of Andrias davidianus ranavirus (ADRV) which was isolated from the Chinese giant salamander contained host factors. Here, a new host factor, the MutS homolog 2 (MSH2), was proved as an important protein that participated in ADRV infection. Expression of MSH2 was stable during ADRV infection in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Viral genomes were extracted according to the Viral Genome Extraction Kit (OMEGA). CGSIV MCP gene primers were designed to evaluate CGSIV DNA replication [ 1 ], and the pMD18T−MCP plasmid (constructed and preserved in this experiment) was used as the standard. CGSIV MCP−F and CGSIV MCP−R were used as upstream and downstream primers, and the absolute quantitative PCR was performed on an ABI 7300 fluorescence qPCR instrument using Takara SYBR ® Premix Ex Taq™ II.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Viral genomes were extracted according to the Viral Genome Extraction Kit (OMEGA). CGSIV MCP gene primers were designed to evaluate CGSIV DNA replication [ 1 ], and the pMD18T−MCP plasmid (constructed and preserved in this experiment) was used as the standard. CGSIV MCP−F and CGSIV MCP−R were used as upstream and downstream primers, and the absolute quantitative PCR was performed on an ABI 7300 fluorescence qPCR instrument using Takara SYBR ® Premix Ex Taq™ II.…”
Section: Methodsmentioning
confidence: 99%
“…Ranaviruses (family Iridoviridae, Alphairidovirinae, genus Ranavirus) are large, double−stranded DNA viruses that infect a variety of ectothermic vertebrates, such as amphibians, reptiles, and fish [ 1 , 2 , 3 , 4 ]. The Chinese giant salamander is the largest amphibian in the world and has great ecological and commercial value.…”
Section: Introductionmentioning
confidence: 99%
“…Each qPCR mixture contained 1 μL of cDNA, 5 μL of SYBR Premix (2×), 1 μL of primers (0.5 μL for each primer), and 3 μL of ultrapure water. The qPCR conditions were conducted as described previously [15]. The β-actin gene of S. chuatsi was used as an internal control.…”
Section: Experimental Detection Of Degs By Rt-qpcrmentioning
confidence: 99%
“…Viral genomes were extracted using the Viral Genome Extraction Kit (omega, Norcross, USA). Using the pMD18T-MCP plasmid as the standard, CGSIV MCP gene primers were designed to evaluate CGSIV DNA replication [22]. qMCP-F/R was used as upstream and downstream primers, and the copy number of viral genomic DNA was determined by absolute quantitative PCR on an ABI 7300 PCR instrument using Takara SYBR ® Premix Ex Taq™ II.…”
Section: Qpcr Was Used To Detect the Copy Number Of Viral Genomic Dnamentioning
confidence: 99%
“…However, host factors have not revealed the mechanism involved in infection replication. At present, some host factors, such as IRF, Uba2, and MSH2, are involved in virus replication in the studies of ranavirus [21][22][23], but the role of DNAJA4 in ranavirus infection has not been reported. In addition, only the effects of CGSIV MCP on CGSIV infection have been reported [20], and no studies have found that host factors are involved in the replication of CGSIV infection.…”
Section: Introductionmentioning
confidence: 99%